Penerapan Asas Pemilu Terhadap Electronic Voting (E-Voting) Pada Pemilu Tahun 2024 - Mhd Ansor Lubis; Wenggedes Frensh; Fitri Yanni Dewi Siregar (Jurnal Ilmiah Penegakan Hukum, 2022)
This study aims to determine the implementation of the E-voting electoral system (Electronic Voting) which is a new method in general elections in Indonesia, the use of the E-voting system (Electronic Voting) later in the 2024 election is a step forward to realize the election principle, namely Luber Jurdil. The use of the conventional system in the previous election was still considered ineffective and in the end gave birth to various problems such as the inaccuracy of the vote count results, it was suspected that there were voters who chose more than one pair of candidates, took a long time to determine the results of the general election, used a lot of human resources. So from these problems, a new system is needed to be able to maximize the electoral system so that the Luber Jurdil principles are implemented. The research method used in this research is normative juridical by using a statutory approach and a conceptual approach to a legal issue that is currently relevant. And is prescriptive. The results of the study conclude that the E-voting system in general elections is a system that is more effectively used and has fulfilled the election principle, namely Luber Jurdil, so that in the implementation of E-voting a special and explicit regulation can be formed, both in the form of laws and regulations. Perpu. So that later in the implementation it has regulations and legitimacy that are binding and clear in accordance with Pancasila and the 1945 Constitution